Dermatophytosis in Al-Gabal Al-Akhader - Abdelkafe, Azza s.; Nasib, Muftah A. (Al-Mukhtar Journal of Sciences, 2012)
A study was conducted to survey some species of land snails in AL-Jabel El-Akhder area, and The damage caused by feeding of Theba pisana on cabbage plant Brassica This work was planned to know the causative fungal agents of dermatophytosis and the rate of distribution of this disease in Al-Gabal Al-Akhdar (El-Beida), Libya. A total of 253 cases of skin infection were collected from the dermatology unit at El-Thawra hospital, El-Beida, Libya. Our results showed that young ages were more liable to infection than adults and incidence of infection was higher in males than females specially in group (1-10) years, while in the rest of all age groups from (10 upto more than 40 years) the incidence were higher in females than males. Patients involved in this study represented different occupations. The higher incidence was recorded between school children. Our finding revealed the identification of three genus:genus Microsporum, where 42 (35.3%) strains of M. canis were isolated. Genus Trichophyton where many species were isolated T. violacenm 25 (21%), T. rubrum 24 (20%). T. verrucosum 10 (8.4%), T. mentagroohytes 4 (3.4%), T. schoenleinii and T. tonsurans 3 for each one (2.5%). And genus Epidermophyton in which 8 strains were obtained (6.7%) and identified as Epi. Floccosum. Scalp infection was the most common clinical finding in this work with higher incidence in males than females followed by Tinea corporis, Tinea unguium, Tinea barbae, Tinea pedis and Tinea cruis. Concerning the sensitivity of isolated fungi to different antifungal agents it was found that all isolates were sensitive to Ketoconazol, Clotrirmazol and Itraconazol while showed resistance to the rest of antifungal agents which are used in this study.